Learning DevOps : continuously deliver better software : learn to use some of the most exciting and powerful tools to deliver world-class quality software with continuous delivery and DevOps : a course in three modules.: continuously deliver better software : learn to use some of the most exciting and powerful tools to deliver world-class quality software with continuous delivery and DevOps : a course in three modules. (2016) - Verona, Joakim; Swartout, Paul; Duffy, Michael
No abstract available